A DEIXIS ANALYSIS OF SONG LYRICS IN HELLO BY ADELE - Nia Kurniati; Acep Haryudun (PROJECT (Professional Journal of English Education), 2021)
The main purpose of this research is to analyze three types of deixis in Adele’s song lyrics. Then, the song lyrics can be analyzed using pragmatic approach, especially about deixis. Then, the song lyrics can be analyzed using pragmatic approach, specifically about deixis. This research applied descriptive qualitative methodThis research applied descriptive qualitative method. The researcher elects lyrics of the most popular songs of Adele’s Album 25. The data ware taken from one of three song lyrics in Adele’s album 25 entitled Hello for identifying and classifying the deixis into their types (person deixis, spatial deixis, and temporal deixis). Based on the results and discussion can be concluded that all deixis found in song lyrics, there are 53 words include of kinds of deixis. the person deixis was found on  adele’s song as the most dominant type (43 deictic words or 75%). Second position, deixis spatial is the most found (9 deictic words or 17%), and in the last position is temporal deixis (4 deictic words or 8%)